Airfoil Improvement on Horizontal Axis Wind Turbine Suitable for Local Construction in Underdeveloped Countries - Miguel, João Carlos Tavares (2019)
This dissertation purpose is to study the impact that a geometry modification of a wind turbine rotor imposes on its performance. The studied wooden rotor, with a diameter of 1.2 m, belongs to a family of small wind turbines that are built by unskilled persons using hand tools with the guidelines of Hugh Piggott. Due to its inaccuracy, the production process delivers a geometry with sharp leading edges. For the performance of an airfoil, the leading edge is one of the most important characteristics to take in mind, and so, the goal of this dissertation was to smooth the airfoils leading edge towards the lower surface in order to widen the ????- ?? curve of the rotor. To do so, numerical methods were employed to assess such modification on the performance, in a way that the technique could be later applied on the rotor using nothing but hand tools. In a previous investigation, the same rotor here approached in this dissertation, was numerically and experimentally studied for the following windspeeds: 3.0; 3.7; 4.4; 5.5; 7.2 e 7.7 m/s. In the same study, a digital scan was performed on the rotor, one for each blade, resulting in 6 different cross sections each with its chord and incidence angle. The three blades present geometric differences. Having these airfoils characteristics, the QBlade software was used for the design and analysis of the new modified airfoils based on the original Piggott airfoils. The software also allows for rotor design and uses the Blade Element Momentum Theory for the analysis of horizontal axis wind turbines. The performance of both rotors was approximated by averaging the performance of three ideal rotors, each consisting of three identical blades 1,2 and 3. The new airfoils regarding blade 1 and 3, presented better aerodynamic efficiency performance compared to the Piggott airfoils, whereas blade 2 new airfoils did not exhibited any significant improved performance compared to the Piggott airfoils.The dimensionless simulations results from QBlade, portrayed that the averaged rotor with the modified airfoils present better power coefficient (????) for high values of ?? (ratio between the tangential velocity of the blade tip and the free stream windspeed) when compared to the averaged rotor with the Piggott airfoils. For a constant rotational speed of 500 RPM, the new rotor remarkably withdraws more energy from the flow for low windspeeds. In a hypothetical approach of a optimized turbine production made up by the best modified airfoils, the optimized rotor simulations showed a significant better performance for high values of ??,as well as higher maximum ???? than the ones from the averaged rotor with the modified airfoils.